Dog Man and Cat Kid - Pilkey, Dav, 1966-; Beard, George (Fictitious character); Hutchins, Harold (Fictitious character) (New York : Graphix, 2018)
Dog Man now has a furry feline sidekick, and together they have a mystery to sniff out. When a new kitty sitter arrives and a glamorous movie starlet goes missing, it's up to Dog Man and Cat Kid to save the day. Will these heroes stay hot on the trail, or will Petey the world's most evil cat send them barking up the wrong tree?
3.0
3-6
Keywords: Police -- Juvenile fiction; Dogs -- Juvenile fiction; Cats -- Juvenile fiction; Heroes -- Juvenile fiction; Police -- Comic books, strips, etc. -- Fiction; Dogs -- Comic books, strips, etc. -- Fiction; Cats -- Comic books, strips, etc. -- Fiction; Heroes -- Comic books, strips, etc. -- Fiction; Humorous comics; Graphic novels; Comics (Graphic works)